Observations and measurements of boric acid precipitation scenarios. (August 2016) - Vaghetto, Rodolfo; Childs, Mason; Kee, Ernie; Hassan, Yassin A.
Abstract: During a Loss of Coolant Accident (LOCA) in a Light Water Reactor (LWR), the safety injection system injects borated water into the core. The continuous vaporization of the water in the core can increase the concentration of boric acid in the core, to where the boric acid reaches the solubility limit and precipitates. This becomes more likely when the liquid water supply is obstructed due to, for example, debris accumulation. Questions have been raised regarding this and other ways in which boric acid precipitate in the core can affect the coolant flow. A testbed was designed and constructed for observing the behavior of borated water under the combined effects of the boiling and the boric acid precipitation (BAP) and for measuring boric acid concentration during different scenarios. The facility consisted of a transparent polycarbonate vertical pipe in which 41 heated rods were installed to enable the water to reach saturation temperature and to maintain a specified boil-off rate. The layout and geometry of the experimental apparatus were designed to emulate a simplified core of a Pressurized Water Reactor (PWR). The test scenarios varied with respect to thermal power, injection location, and test section configuration. The observations and measurements conducted demonstrated that, even at concentrations above the solubility limit, no appreciable deposition of the solid precipitate was possible, especially in the regions at higher power density. Precipitate particles were observed to be relatively smaller than the channels' size, and no impact on the coolant behavior was observed. The rate of increase of concentration of boric acid was possibly slowed down by the loss of boric acid in entrained liquid droplets through the exhaust. The results obtained provided a better understanding of the flow behavior in the core in presence of high concentrations of boric acid and may be of immediate use for utilities and the research community performing evaluations of the long-term core coolability. Highlights: Visualization of boric acid solutions under boiling conditions have been conducted. Results obtained have proven flow is not appreciably impacted by the precipitate. Uniform concentration is expected due to the high mixing in the core. Deposition has been observed in regions of low power density or top of the core.